Multiplex Polymerase Chain Reaction for diagnosis of gastrointestinal tuberculosis. Issue 1 (17th October 2018) - Malik, Sarthak; Sharma, Kusum; Vaiphei, Kim; Dhaka, Narendra; Berry, Neha; Gupta, Pankaj; Sharma, Megha; Mallick, Bipadabhanjan; Kochhar, Rakesh; Sinha, Saroj K
Abstract : Background and Aim: To evaluate the role of multiplex polymerase chain reaction (PCR) for diagnosis of gastrointestinal tuberculosis (GITB). Methods: This was a prospective observational study conducted from July 2015 to November 2016 at a tertiary care teaching institution in north India. Fifty individuals with clinically suspected GITB and older than 18 years of age were recruited. Patients underwent radiological investigations, esophagogastroduodenoscopy, or colonoscopy as clinically indicated. Multiple biopsies for tissue diagnosis and PCR were taken. All specimens were subjected to Ziehl Neelsen staining, histopathology, and multiplex PCR using specific primers for genes IS6110, MPB64, and Protein b. The performance of the assay was assessed using a composite reference standard for diagnosis of tuberculosis. It comprised a combination of clinical characteristics and microbiological methods, including smear, Bactenecin (BACTEC) culture, histopathology, and response to antitubercular therapy. Results: A final diagnosis of tuberculosis was made in 32 cases (Duodenal‐4, Ileo‐colonic‐28). The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) of histopathology for the diagnosis of tuberculosis was 28.12, 100, 100, and 43.9%, respectively. The sensitivity, specificity, PPV and NPV of BACTEC Mycobacteria Growth Indicator Tube (MGIT) culture for the diagnosis of tuberculosis was 9.3, 100, 100, and 38.29%, respectively. The sensitivity, specificity, PPV, and NPV of multiplex PCR for the diagnosis of tuberculosis was 87.5, 100, 100, and 86.2%, respectively. Conclusion: Multiplex PCR using specific primers for genes IS6110, MPB64, and Protein b had a higher sensitivity compared to conventional techniques for the diagnosis of GITB. Abstract : In this prospective study, multiplex PCR using specific primers for genes IS6110, MPB64, and Protein b had a higher sensitivity compared to conventional techniques for the diagnosis of gastrointestinal tuberculosis.